2021
DOI: 10.11609/jott.6302.13.5.18313-18318
|View full text |Cite
|
Sign up to set email alerts
|

Marine mammal strandings in the northern Palk Bay from 2009 to 2020

Abstract: Globally, the marine mammal population has been under threat due to various human activities.  Data on stranding of these animals that are important for effective conservation planning and management, however, are not available in most of the developing countries.  This paper presents observations on marine mammal strandings in northern Palk Bay, the southeastern coast of India over the last decade.  In total, 21 stranding events consisting of 23 marine mammals were observed from 2009 to 2020.  These stranded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Megaherbivores (e.g., sea cows and sea turtles) and macroherbivores (e.g., fishes) have a high grazing effect on seagrass shoot density, which has often resulted in shoot declines (Burkholder et al, 2013; Lal et al, 2010). Both GoMMNP and PB reported the presence of sea cows ( Dugong dugon ) and sea turtles, as well as their use of seagrass meadows for foraging (Balaji & Sekar, 2021; Bhupathy & Saravanan, 2006). In the GoMMNP, strong waves and currents have been documented to produce periodic disruptions to seagrass ecosystems by uprooting seagrass, resulting in enormous green tides and massive amounts of seagrass deposits onshore (Ramesh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Megaherbivores (e.g., sea cows and sea turtles) and macroherbivores (e.g., fishes) have a high grazing effect on seagrass shoot density, which has often resulted in shoot declines (Burkholder et al, 2013; Lal et al, 2010). Both GoMMNP and PB reported the presence of sea cows ( Dugong dugon ) and sea turtles, as well as their use of seagrass meadows for foraging (Balaji & Sekar, 2021; Bhupathy & Saravanan, 2006). In the GoMMNP, strong waves and currents have been documented to produce periodic disruptions to seagrass ecosystems by uprooting seagrass, resulting in enormous green tides and massive amounts of seagrass deposits onshore (Ramesh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1950s, CMFRI has documented approximately 380 stranding cases (Jeyabaskaran et al, 2013;Balaji & Sekar, 2021). Jeyabaskaran et al (2016), analyzed stranding records from 1800-2016 along the peninsula and found a total of 25 species with finless porpoises having the lowest percentage of strandings.…”
Section: Current Researchmentioning
confidence: 99%